Variable stars in local group galaxies – IV. RR Lyrae stars in the central regions of the low-density galaxy Crater II. Issue 4 (28th June 2018) - Monelli, M; Walker, A R; Martínez-Vázquez, C E; Stetson, P B; Gallart, C; Bernard, E J; Bono, G; Vivas, A K; Andreuzzi, G; Dall'Ora, M; Fiorentino, G; Dorta, A
ABSTRACT: We present a search and analysis of variable stars in the recently discovered Crater II dwarf galaxy. Based on B, V, I data collected with the Isaac Newton Telescope (FoV∼0.44 deg 2 ), we detected 37 variable stars, of which 34 are bone-fide RR Lyrae stars of Crater II (28 RRab, 4 RRc, 2 RRd). We applied the metal-independent ( V, B − V ) Period–Wesenheit relation and derived a true distance modulus (μ = 20.30 ± 0.08 mag (σ = 0.16 mag). Individual metallicities for RR Lyrae stars were derived by inversion of the predicted I -band Period–Luminosity relation. We find a mean metallicity of [Fe/H] = −1.64 and a standard deviation of σ _[Fe/H]=0.21 dex, compatible with either negligible or vanishing intrinsic metallicity dispersion. The analysis of the colour–magnitude diagram reveals a stark paucity of blue horizontal branch stars, at odds with other Galactic dwarfs, and globular clusters with similar metal abundances.